The tools, approaches and applications of visual literacy in the Visual Arts Department of Cross River University of Technology, Calabar, Nigeria. Issue 2 (2nd April 2016) - Ecoma, Victor
Abstract: The paper reflects upon the tools, approaches and applications of visual literacy in the Visual Arts Department of Cross River University of Technology, Calabar, Nigeria. The objective of the discourse is to examine how the visual arts training and practice equip students with skills in visual literacy through methods of production, materials and techniques. The research purpose is to show how the final year students trained in visual arts are able to create works of art with the primary goal of communicating meanings visually to the viewers. The photographed student's works ranged from sculpture showing traditional drummers, spiders as a motif for creative exploration in painting, graphic poster design emphasizing economy of time, two decorative ceramic pieces and a woven utilitarian textile fibre. For the students to have successfully communicated visually they ought to be able to effectively manipulate the art elements and principles which makes it possible to encode meanings to their works and the viewers been able to decode same. The research results evident in the students photographed works, show that students are able to organize their ideas in a visual form and are able to use images to convey meanings in their works which viewers can relate to. In this regard, the students are able to encode and decode meanings in visual forms which are fundamental to visual literacy as practiced in visual arts. The correlation between visual arts training and visual literacy is established through the observation of a long teaching career which record student's behaviour in the creative process and its results in productions. Findings show that students training in the visual arts equip them to develop their perceptual and conceptual faculties through learning, to use appropriate visual vocabularies in decoding and encoding visual messages. This also equips them with a holistic education in the cognitive, affective and psychomotor domains. It is therefore concluded that the visual arts training is critical to the acquisition of visual literacy skills and it is recommended that visual arts should be more broadly taught in schools as a foundation for visual literacy.